PEMBELAJARAN DARING : ADVERSITY QUOTIENT DAN SELF DIRECTED LEARNING PADA SISWA - Lilis Ratnasari; Asma Wardah Islamiyyah (Jurnal Sosial Humaniora dan Pendidikan, 2023)
Online learning is an alternative form of learning to overcome challenges in the world of education, which will produce different levels of effectiveness for students due to various factors, both internal and external. The purpose of this study was to empirically examine the relationship between adversity quotient and self-directed learning in students who study daring. The participants of this study were 120 students studying daring. Simple regression analysis was used as a data analysis technique in this study. The results of this study showed a significant correlation of 0.584. The higher the adversity quotient, the higher the self-directed learning in students who learn daring, and vice versa, the lower the adversity quotient, the lower the self-directed learning in students who does online learning.